Análise da gestão do processo de desenvolvimento de produtos em empresas fornecedoras de bens de capital para o setor sucroalcooleiro - Onoyama, Marcia Mitiko (Universidade Federal de São Carlos, 2011)
This thesis aims to analyze the product development process (PDP) management of companies, medium and large sized, from São Paulo State that manufactures capital goods for sugar alcohol sector. The field research included quantitative (survey) and qualitative (case studies) procedures. In the first part, it was collected data through in loco interviews with a sample of 31 companies. The data were analyzed in order to characterize these companies, to test possible correlations between the characteristics of PDP management and the results of PDP performance and to cluster companies with similar characteristics in terms of formalized PDP activities. The correlation analysis identified that the presence of formal mechanisms for evaluating and selecting projects, the quality of strategic and operational PDP activities, the PDP team structure, multi-functional integration, the company's ability to design new products, the team leader s ability to design new product, the existing training programs and monitoring of the personnel involved in the PDP and the use of methods and tools to support the PDP operational dimension, may favor the results of PDP performance. Cluster analysis generated three clusters, depending on the formalization of PDP activities. In general, it is observed that companies have more structured the operational dimension of PDP management than the strategic dimension, in terms of formalized procedures and employed methods and support tools. To deepen the understanding of the practices and the knowledge of strategic dimension in these companies, the second part of the study comprised case studies in seven companies, selected according to cluster analysis. In general, efforts on activities of identifying real opportunities for new products (concrete case) and individual proposals analysis are verified in these companies, focusing mainly on short and medium term. In addition, there is limited use of methods and tools to support the strategic dimension of PDP management, related to the planning and decision making. Only large companies, auxiliary equipment suppliers of electric and electronic technology, works with a long-term horizon (5 to 10 years) in the elaboration of the planning of new products projects portfolio. The confrontation between the theoretical framework on the PDP management and field research were allowed to develop recommendations to strengthen the strategic dimension of PDP management in these companies.
Keywords: Processo de desenvolvimento de produtos; Planejamento estratégico de novos produtos; Empresas de bens de capital - sucroalcooleiro; ENGENHARIAS::ENGENHARIA DE PRODUCAO